Production, Preservation, and Disclosure of Metadata - Beckham, J. Brian (Science and Technology Law Review, 2006)
As the use of information technology increasingly pervades every facet of our personal and professional life, legal practitioners are taking increasing notice of the effect that metadata can have on their practice. In particular, the prevalence of metadata threatens to have a dramatic effect on discovery issues, such as document retention and production. This article endeavors to define and discuss the concept of metadata, and then explore how this new category of information will apply to traditional notions of waiver and privilege. It will then highlight several proposals for the discoverability of metadata, and will conclude with a discussion of the ethical implications for counsel in dealing with electronically transmitted documents.